What is 6/2(1+2)^2
For this problem, you must use PEMDAS so first, you solve the problem inside the parentheses. That leaves you with 6/2(3)^2. Second, you solve any exponents, which leaves you with 6/2*9. Third, you do multiplication and division in the order they appear. In this case, division is first and multiplication is second. After you do the division you have 3*9. To get the answer you multiply 3 and 9 which gives you 27
Find the independent and dependent clauses in the following sentence: If it is raining today, I will wear my jacket.
The independent clause is the one that can stand on its own. Therefore the independent clause in this sentence is: I will wear my jacket The dependent clause is the one that does not form a complete sentence on its own. Therefore, the dependent claus in this sentence is: If it is raining today
(x-1)[(x+3)+(3/x-1)] = [(4-x)/(x-1)](x-1) Solve for X
First, distribute x-1 on both sides. This gives you (x-1)(x+3)+3 = (4-x) Second, foil the left side. This gives you x^2+2x-3+3 = 4-x Third, combine like terms. This gives you x^2+3x-4 = 0 Fourth, factor the equation. This gives you (x+4)(x-1) = 0 Last, solve for x+4 = 0 and x-1 = 0. You get the answers x = -4 and x = 1